Perceived Stress and Psychological Impact Among Healthcare Workers at a Tertiaty Hospital in China During the COVID-19 Outbreak: The Moderating Role of Resilience and Social Support - Zhang, Qiaoyang; Dong, Guanzhong; Meng, Weifen; Chen, Zhuoyou; Cao, Yin; Zhang, Min (Frontiers in Psychiatry, 2022)
Aims: To investigate the psychological distress experienced by healthcare workers at a tertiary hospital in Changzhou, China, outside Wuhan, during the early stage if COVID-19. And evaluate the moderating effects of resilience and social support between the relationship of stress and psychological distress. Methods: The study was conducted between February 10-15, 2020, in a non-probabilistic way. The survey included questions regarding the risk of exposure, sociodemographics, perceived stress (PSS-10), resilience (CD-RISC-10), social support (MSPSS), and psychological distress (GHQ-12). We applied the PROCESS macro for SPSS to test the hypotheses that resilience and social support moderated the stress response. In addition, a simple slope analysis was conducted when the interaction effect was statistically significant. Results: 33.6% of participants suffered from psychological distress (GHQ-12≥12). Perceived stress was positively related to psychological distress (r = 0.42, P < 0.001). In addition, resilience (ΔR2 = 0.03, P for interaction ＜0.001) and social support (ΔR2 = 0.01, P for interaction ＜0.01) moderated the stress response. The impact of perceived stress on psychological distress was attenuated when subjects who were resilient (High β = 0.15, P < 0.001; Low β = 0.36, P < 0.001), and perceived stress had less impact on psychological distress when social support was high (β = 0.24, P < 0.001) rather than low (β = 0.34, P < 0.001). Limitations: The cross-sectional design led to a lack of causal relationships between variables. Conclusions: Our data showed that resilience and social support moderated the stress response among HCWs in the pandemic. Suggesting that improving resilience and social support could be appropriate targets to increase HCWs' mental health in the pandemic.